Clio Medica : Acta Academiae Internationalis Historiae Medicinae. Vol. 18 - Marielene Putscher, (Clio Medica ;, 1983)
As periodical of the International Academy of the History of Medicine, this Clio Medica volume contains 17 papers + reviews & notices.